Libraries on the Hill: An Exploratory Study of Canadian Library Associations Advocacy Initiatives - Carr-Wiggin, Merran; Gareau-Brennan, Céline; Carrier, Hélène; McNally, Michael B. (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
This exploratory study analyzes the advocacy practices and outputs of three national associations representing libraries and organizations of various types: the Canadian Association of Research Libraries (CARL) / Association des bibliothèques de recherche du Canada (ABRC), the Canadian Urban Libraries Council (CULC) / Conseil des bibliothèques urbaines du Canada (CBUC), and the Canadian Federation of Library Associations (CFLA) / Fédération canadienne des associations de bibliothèques (FCAB). Data was collected from a variety of sources, including the associations’ websites, records of federal government consultations and lobbying activities. A thematic analysis was conducted using open coding and visual theme mapping, and the results analyzed using Schein’s model for understanding organizational culture. The results provide important insights into publicly available advocacy work by these associations since 2016. By providing the first step of examining advocacy work by Canadian library associations, this study lays the groundwork for further investigation to explore the impact of library association advocacy and to identify successful patterns and strategies for advocacy initiatives in the future.